Malignant Fibrous Histiocytoma of the Head and Neck: CT and MR Imaging Findings - Park, S.-W.; Kim, H.-J.; Lee, J.H.; Ko, Y.-H. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: Malignant fibrous histiocytoma (MFH) is uncommon in the head and neck. The purpose of this study was to investigate CT and MR imaging features of 13 cases of MFH of this area.MATERIALS AND METHODS: Two head and neck radiologists, in consensus, retrospectively reviewed CT (n = 11) and MR (n = 9) images in 13 patients (9 men and 4 women; mean age, 45 years) with histologically proved MFH of the head and neck, paying attention to the location and extent, size, margin, internal architecture, and pattern and degree of enhancement of the lesion. We also investigated if there were any differences in signal-intensity characteristics on MR images, according to different histologic subtypes.RESULTS: All lesions were seen as well-defined (n = 2) or ill-defined (n = 11), aggressive masses with a mean size of 4.9 cm. The tumors were primarily located in the sinonasal cavity in 6, the soft tissue of the face and neck in 5, the oral cavity in 1, and the orbital roof in 1. One lesion arose in the bones with background fibrous dysplasia. Twelve lesions invaded the adjacent soft tissues, and bone destruction was seen in 11 lesions. The attenuation, signal intensity, and enhancement pattern of the lesions were nonspecific except for those of myxoid MFH.CONCLUSIONS: Although rare, MFH of the head and neck is an aggressive tumor that arises most commonly in the sinonasal tract and is frequently associated with soft-tissue invasion and bone destruction on CT and MR images.